Missed opportunities to reduce vertical transmission of congenital syphilis (Research, Society and Development, 2024)
Introduction: Congenital syphilis is a systemic bacterial infection transmitted transplacentally or through baby contact with lesions in the birth canal that has been a public health concern for decades. Although it is an infection that is easy to diagnose and treat, when not diagnosed and treated in a timely manner, it can lead to more serious consequences. Objective: The objective was to carry out research to evaluate missed opportunities to reduce the vertical transmission of congenital syphilis. Methods: Observational, cross-sectional and analytical study carried out in a Philanthropic Maternity Hospital in Aracaju – SE, from 2022 to 2023. Data were collected from the physical records of patients with congenital syphilis, in the outpatient clinic to follow up newborns diagnosed and followed up with this condition. disease according to the definition criteria of the Ministry of Health. Results: 264 children had a missed opportunity with a diagnosis of congenital syphilis and 6% of them with neurosyphilis. The average gestational age was 38.73 weeks, and 79% were born with adequate weight. Non-treatment or inadequate treatment in pregnant women was 49%. Untreated mothers had statistical significance with lower birth weight and fewer prenatal consultations. The inadequacy of maternal treatment was related to factors such as inadequate intervals and incorrect doses. Conclusion: it is concluded that prenatal behavior was related to the socioeconomic vulnerability of the studied population and maternal non-treatment was associated with unfavorable outcomes in the newborn.